McKittrick Wheelock Syndrome Secondary to Adenocarcinoma of the Rectum. Case Report and Diagnostic Considerations - Claudia Alejandra Aceves Quintero; Santiago Taracena Pacheco; Itzel Vela Sarmiento (Journal of Coloproctology, 2023)
Introduction McKittrick-Wheelock syndrome is a rare entity characterized by chronic diarrhea, acute kidney injury, and hydroelectrolytic imbalance associated with a large rectal tumor, frequently a villous adenoma.